Implementation Of The Congregational Dhuha Prayer Program In The Formation Of Students' Discipline Character In SMP Muhammadiyah 16 Lubuk Pakam - Azhari, Aidil; Ananda, Sofi; Khairani, Farida; Setiawan, Hasrian Rudi (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
This research uses a descriptive qualitative approach. The population collected in this study were students of class VIII SMP Muhammadiyah 16 Lubuk. The sample for this research was 35 grade VIII students who were taken using student and teacher interview techniques, direct observation of the research location, and research documentation. To obtain data on the Implementation of the Dhuha Prayer Program for class VIII students, researchers used interview techniques, practice, and questionnaires or questionnaires. Meanwhile, the way to implement Discipline Character Formation is by direct application during the hours of Duha prayer activities. Based on the findings of the researchers during the research at SMP Muhammadiyah 16 Lubuk Pakam, there were several findings that the researchers obtained in accordance with the existing problems. Implementation and Training for the Implementation of the Congregational Dhuha Prayer Program in Forming the Discipline Character of Students at SMP Muhammadiyah 16 Lubuk Pakam. In providing material for the discipline of Duha prayer and its training, in this case the researcher specializes in class VIII SMP, it is easy to accept material and easy to self-discipline in carrying it out and feels that he has to be even better at disciplining his Duha prayer activities. enthusiastic because students are not used to disciplining themselves for Duha prayer for certain reasons such as the time for Duha prayer which is determined by the school to take part of their break time